2018
DOI: 10.3390/su10113830
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Air Quality: A Bibliometric Study

Abstract: What are the actual trends in Indoor Air Quality (IAQ), and in which direction is academic interest moving? Much progress has been made in identifying and mitigating indoor pollutants, due to both prevention campaigns (e.g., smoking bans) and greater control of product emissions. However, IAQ is still of interest and the future trends are unknown. In this study, a thorough bibliometric analysis was conducted on the scientific literature available on the Web of Science database with CiteSpace from 1990 until to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…In 2018, Pierpaoli and Ruello published a paper on the bibliometric study on the IAQ [49]: the authors asked the question "What are the actual trends in Indoor Air Quality (IAQ), and in which direction is academic interest moving?" Starting from that, the authors analyzed the worldwide literature from 1990 to 2018, using the Web of Science as a database.…”
Section: Rapp Istisanmentioning
confidence: 99%
“…In 2018, Pierpaoli and Ruello published a paper on the bibliometric study on the IAQ [49]: the authors asked the question "What are the actual trends in Indoor Air Quality (IAQ), and in which direction is academic interest moving?" Starting from that, the authors analyzed the worldwide literature from 1990 to 2018, using the Web of Science as a database.…”
Section: Rapp Istisanmentioning
confidence: 99%
“…And for the research of Carbon Capture and Storage, Qiu and Liu demonstrated it by knowledge mapping, showing three main topics, carbon emissions with environment protection, R&D activities and social practical issues (Qiu & Liu, 2018). Furthermore, Pierpaoli and Ruello detected the focus of attention of indoor air quality during different years (Pierpaoli & Ruello, 2018) Research trends of renewable energy deserve more summaries in terms of different forms of clean power supply. Hence, in this paper, literature with the theme of "Offshore Wind Power" from Clarivate Analytics' Web of Science Core Collection were searched and gathered, then CiteSpace was used for visual bibliometric analysis to explore the development history and law, along with the high contributors in terms of country/region and institution on what we focus.…”
Section: Literature Reviewmentioning
confidence: 99%
“…CiteSpace is a visual analysis software developed by Professor Chen from Drexel University in the United States based on the Java language, which has been iteratively updated to version 5.2.R2 [24]. At present, many researchers use Citespace software to conduct mapping knowledge domains research, and have achieved good results [25][26][27][28]. This paper uses CiteSpace5.2.R2 software to visualize the cooperative network, co-occurrence network and co-cited cases, obtaining relevant mapping knowledge domains.…”
Section: Methodsmentioning
confidence: 99%